2003
DOI: 10.4049/jimmunol.170.7.3637
|View full text |Cite
|
Sign up to set email alerts
|

B7-H1 (Programmed Death-1 Ligand) on Dendritic Cells Is Involved in the Induction and Maintenance of T Cell Anergy

Abstract: In an effort to identify immunoregulatory molecules on dendritic cells (DC), we generated and screened for mAbs capable of modulating the T cell stimulatory function of DC. A particularly interesting mAb was mAb DF272. It recognizes monocyte-derived DC, but not blood monocytes or lymphocytes, and has profound immunomodulatory effects on DC. Treatment of DC with intact IgG or Fab of mAb DF272 enhanced their T cell stimulatory capacity. This effect on DC was accompanied by neither an up-regulation of costimulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
167
1
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 246 publications
(185 citation statements)
references
References 30 publications
15
167
1
2
Order By: Relevance
“…In line with other studies using tolerogenic DC [11,12], we have previously reported that this model involves the induction of non-deletional tolerance [13].…”
Section: Hyporesponsive T Cells Display Reduced Migratory Ability Andsupporting
confidence: 86%
“…In line with other studies using tolerogenic DC [11,12], we have previously reported that this model involves the induction of non-deletional tolerance [13].…”
Section: Hyporesponsive T Cells Display Reduced Migratory Ability Andsupporting
confidence: 86%
“…25 We and others have shown a strong association between B7-H1 expression and bad prognostic factors in several malignancies. [16][17][18][19]35 In the present study the strong link observed between B7-H1 and Ki-67 markers suggests that the low patients' survival, 25 seen in highly proliferating tumors, may be the results of B7-H1 induction in proliferating tumor cells leading to the inhibition of the immune system [10][11][12]36 and thereby providing more advantages for the tumors to grow.…”
Section: Discussionmentioning
confidence: 86%
“…[9][10][11][12] It has been shown to be directly involved in the protection of cancer cells from activated T lymphocytes. 13 The expression of this molecule has been described in several malignancies including ovary, colon, melanoma and carcinoma of the lung.…”
mentioning
confidence: 99%
“…It would be of interest to ascertain whether differences in the level of B7-H1 among anatomically distinct (bone marrow vs spleen) dendritic cells contribute to suboptimal immune responses. B7-H1 expression by dendritic cells has been implicated in the induction and maintenance of T cell anergy and tolerance (35,36). Tumor myeloid dendritic cells express high levels of B7-H1, and the blockade of B7-H1 engagement enhances infiltration of effector CD8 ϩ T cells, thereby conferring improved antitumor immunity (37).…”
Section: Discussionmentioning
confidence: 99%